Mental Health Problems, History of Drug Use, and Violent Offending Are Associated With Increased Suicide Risk in Imprisoned Females - Zhong, Shaoling; Zhu, Xiaomin; Mellsop, Graham; Guo, Huijuan; Chen, Yanan; Luo, Chenyuli; Li, Qiguang; Zhou, Jiansong; Wang, Xiaoping (Frontiers in Psychiatry, 2019)
Background: In western countries, imprisoned females are at high risk for suicide, but the risk in Chinese imprisoned females has not been well established. The aim of this study was to clarify the suicide risk and its correlates among imprisoned females in China. Methods: In this cross-sectional study subjects were recruited from the Female Prison of Hunan province, China. A standardized questionnaire was used to collect socio-demographic and criminological data. The Suicidality module of the Mini International Neuropsychiatric Interview (MINI) 5.0 and 12-item General Health Questionnaire (GHQ-12) were used to assess suicide risk and mental health problems respectively. Ordinal logistic regressions were used to identify independent factors associated with increased suicide risk. Results: A total of 2709 imprisoned females completed the survey questionnaire. Twenty per cent were rated as presenting suicide risk. Mental health problems (OR=1.21, 95%CI=1.00-1.47), self-reported help-seeking for mental health problems (OR=1.69, 95%CI=1.11-2.56), violent offending (OR=1.69, 95%CI=1.37-2.09), history of drug use (OR=1.46, 95%CI=1.15-1.84), family history of mental disorders (OR=1.57, 95%CI=1.10-2.23), marital status (OR=1.29, 95%CI=1.05-1.58) and low educational level (OR=1.36, 95%CI=1.11-1.67) were independently associated with increased suicide risk. Conclusion: One-fifth of the imprisoned females are at risk for suicide. This study highlights the importa